Sensory and Chemical Characteristics of Solid Brem with The Addition of Gedong Gincu Mango Juice (Mangifera Indica L. Var. Gedong Gincu) - Lisa Ainurohmah; Rosy Hutami; Nusyawal Nacing (Indonesian Journal of Applied Research (IJAR), 2023)
Brem is a type of advanced processed food from fermented white glutinous rice. This study aims to determine the characteristics of solid brem with the addition of Gedong Gincu mango juice. This research uses a one-factor, completely randomized design (CRD) with three levels of treatment with a comparison of white sticky tape juice and Gedong Gincu mango juice, namely A1 (85%:15%), A2 (75%:25%), and A3 (65%:35%). As well as testing paired T-tests for selected products and control. The data analysis used is ANOVA with Duncan advanced test (α=0,05). Based on the results of research solid brem addition of Gedong Gincu mango juice affects the sensory quality (color (3,53-8,44), flavor (5,61-6,79), and appearance (5,44-7,85)), hedonic (color (4,97-7,29), aroma (6,04-7,30), texture (6,34-7,79), and overall (6,41-7,53)), and chemical (water content (18,31%-20,71%), carbohydrates as starch (2,63%-9,17%), acidity (9,51%-17,85%), and vitamin C (2,25 mg/100g-3,02 mg/100g)). However, the addition of Gedong Gincu mango juice did not affect the sensory quality (aroma (5,92-6,45), taste (6,77-7,60), and texture (7,41-7,75)), hedonic (taste (6,34-7,16)), and chemical (ash content (1,45%-4,06%), and water-insoluble part (3,61%-4,15%)). Further test results T-test sample A1 and control showed parameters of color, aroma, and appearance (sensory quality); color, aroma, and taste (hedonic); and the value of water content, ash content, carbohydrates, acid degrees, and vitamin C has no significant effect with the addition of Gedong Gincu mango juice. In contrast, the parameters of taste, flavor, texture (sensory quality), texture and overall (hedonic), and water-insoluble part significantly affect the addition of Gedong Gincu mango juice